Quadratic 2-step Lie algebras: Computational algorithms and classification. (September 2019) - Benito, Pilar; de-la-Concepción, Daniel; Roldán-López, Jorge; Sesma, Iciar
Abstract: Taking into account the theoretical results and guidelines given in this work, we introduce a computational method to construct any 2-step nilpotent quadratic algebra of d generators. Along the work we show that the key of the classification of this class of metric algebras relies on certain families of skewsymmetric matrices. Computational examples for d ≤ 8 will be given.